2018
DOI: 10.1016/j.ffa.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Multi-twisted codes over finite fields and their dual codes

Abstract: Let Fq denote the finite field of order q, let m1, m2, · · · , m ℓ be positive integers satisfying gcd(mi, q) = 1 for 1 ≤ i ≤ ℓ, and let n = m1 + m2 + · · · + m ℓ . Let Λ = (λ1, λ2, · · · , λ ℓ ) be fixed, where λ1, λ2, · · · , λ ℓ are non-zero elements of Fq. In this paper, we study the algebraic structure of Λ-multi-twisted codes of length n over Fq and their dual codes with respect to the standard inner product on F n q . We provide necessary and sufficient conditions for the existence of a self-dual Λ-mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…As f j (x) is irreducible, we have F j is a field. As (m i , p) = 1, from [9] we have M i = r j=1 l ji F j , where l ji F j = (0) if l ji = 0 and l ji F j = F j otherwise. Hence, we have…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…As f j (x) is irreducible, we have F j is a field. As (m i , p) = 1, from [9] we have M i = r j=1 l ji F j , where l ji F j = (0) if l ji = 0 and l ji F j = F j otherwise. Hence, we have…”
Section: Preliminariesmentioning
confidence: 99%
“…They have shown that there are codes with better parameters in this class compared to the other known linear codes. Later, Sharma et al [9] described the algebraic structure of multi-twisted codes and its dual codes. They have obtained some conditions under which the multi-twisted code is a linear complementary dual (LCD).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic and constacyclic linear codes have been generalized in various forms. Quasi-cyclic (QC) codes, quasi-twisted (QT) codes, generalized quasi-cyclic (GQC) codes, multi-twisted (MT) codes are important generalizations among cyclic and constacyclic codes which have attracted many researchers; see [14], [3,4,8], [2,6,13] and [1,10] respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For a linear code C , if C ∩ C ⊥ = {0}, then we called it an LCD code. LCD codes over finite fields were mainly studied in [20]- [29]. Shi et al studied LCD codes over Galois rings, and obtained some classes of asymptotically good LCD codes [30].…”
Section: Introductionmentioning
confidence: 99%